Protocol for measuring the auxin-induced changes of m6A modification - Bin Li; Yixing Li; Lei Li; Linjun Cai; Lan Li; Li Li; Chongsheng He (STAR Protocols)
Summary: Plant m6A modification is highly dynamic, with plant hormones serving as key regulators that induce these dynamics. Here, we present a protocol for detecting phytohormone-induced changes in m6A modification using RNA dot blot and m6A sequencing (m6A-seq) techniques. We describe steps for the auxin treatment, RNA dot blot and m6A-seq library preparation, and data analysis. This protocol holds potential applications for analyzing changes in m6A modification induced by plant hormones.For complete details on the use and execution of this protocol, please refer to Bin et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.